What drives international bank flows? Politics, institutions and other determinants - Elias Papaioannou (European Central Bank (ECB), 2005)
This paper uses a large panel of bilateral bank flow data to assess how institutions and politics affect international capital -bank in particular- flows. The following key findings emerge: 1) The empirical "gravity" model is the benchmark in explaining the volume of international banking activities. 2) Conditioned on standard gravity factors (distance, GDP, population), well-functioning institutions are a key driving force for international bank flows. Specifically, foreign banks invest substantially more in countries with i) uncorrupt bureaucracies, ii) high-quality legal system, and iii) a non-government controlled banking system. 3) Beyond institutions, politics exert also a firstorder impact. 4) The European Integration process has spurred cross-border banking activities between member states. These results are robust to various econometric methodologies, samples and the potential endogeneity of institutional characteristics. The strong institutions/politics-bank flows nexus has strong implications for asset trade and international macro theories, which have not modelled these relationships explicitly.
Keywords: F34; F21; G21; K00; 330; banks; Capital flows; institutions; law and finance; politics; Internationaler Zahlungsverkehr; Internationale Bank; Bankenregulierung; Institutionelle Infrastruktur; Gravitationsmodell; Schätzung; Welt